1999
DOI: 10.2337/diacare.22.10.1708
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of fingerstick blood glucose measurements with GlucoWatch biographer glucose results in young subjects with type 1 diabetes.

Abstract: This study confirms the accuracy and precision of glucose values as determined using the GlucoWatch biographer in clinic and home settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(88 citation statements)
references
References 0 publications
1
86
0
1
Order By: Relevance
“…approximately 5-20 % of patients suffer from erythema, edema, or skin irritation due to the sensor adhesive. 10,12,13 another disadvantage of cGM is the time lag between the blood glucose value and the interstitial glucose value. The time lag is related to errors in SMBG and is especially accentuated with a higher rate of change of glucose greater than 2 mg/dl/minute (0.1 mmol/l/minute).…”
mentioning
confidence: 99%
“…approximately 5-20 % of patients suffer from erythema, edema, or skin irritation due to the sensor adhesive. 10,12,13 another disadvantage of cGM is the time lag between the blood glucose value and the interstitial glucose value. The time lag is related to errors in SMBG and is especially accentuated with a higher rate of change of glucose greater than 2 mg/dl/minute (0.1 mmol/l/minute).…”
mentioning
confidence: 99%
“…We have evaluated the relationship between BG and glucose extracted from interstitial fluid using a GlucoWatch (Cygnus, Redwood City, CA) biographer. This is an Food and Drug Administrationapproved device used to detect trends and track patterns in glucose levels (3)(4)(5). It works through a process called reverse iontophoresis (6), which allows the biographer to collect glucose samples from subcutaneous interstitial space through intact skin by application of a low-level electric current.…”
mentioning
confidence: 99%
“…The GlucoWatch biographer (Cygnus, Redwood City, CA) provides frequent, automatic, and noninvasive glucose measurements-up to three readings per hour for as long as 12 h after a blood glucose measurement for calibration. Clinical studies in controlled and home environments have demonstrated high accuracy and precision (2,3). The results presented here evaluate the hypoglycemia alert performance in a large and demographically diverse patient population using the biographer both in controlled and normal daily environments.…”
mentioning
confidence: 99%